2013
DOI: 10.1177/2156587213514054
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Harp Therapy During In Vitro Fertilization–Embryo Transfer

Abstract: Harp therapy decreases state, or event-based, anxiety, significantly lowering state scores posttransfer and having a positive effect on acute levels of stress. There was an increased pregnancy rate, but larger sample sizes are needed to evaluate whether harp therapy has an effect on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…A total of 34 studies with 7213 patients overall were included in both the qualitative and the quantitative synthesis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 34 studies with 7213 patients overall were included in both the qualitative and the quantitative synthesis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of infertility was 3.6 years, and the duration was longer than 5 years in 26.4% of the patients. In total, 23 studies reported emotional ratings at baseline . Anxiety, depression, and infertility distress were the most common psychological disorders before the beginning of ART treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19] Moreover, some investigators reported that stress reduction by relaxation training, hypnosis during embryo transfer (ET) and medical clowning after ET improved outcome, 6,[20][21][22][23] but other studies showed that stress reduction therapy did not help to improve pregnancy rate. [24][25][26][27] The controversial findings relating to stress and clinical outcome following IVF treatment may be due to a number of reasons. First, it has been shown that stress level fluctuated during IVF treatment, [7][8][9][10]28 with several studies reporting higher stress during pregnancy testing.…”
Section: Introductionmentioning
confidence: 99%
“…Pre treatment identification of these women will require more detailed investigation of their psychosocial risk factors, evidence of positive and negative emotional adjustments, and detailing factors associated with the presence and absence of maladaptive and adaptive coping strategies. Further studies are required to show that effective treatment strategies exist and can be successfully integrated with psychological profiling of A recent study showed that live harp music being played for 20 minutes during ET is potentially anxiety reducing [28]. This type of 'music therapy' was obviously administered in a different way from in our study and music was used only within the specific context of our study design.…”
Section: Discussionmentioning
confidence: 95%